Quantitative Prediction of OATP‐Mediated Drug‐Drug Interactions With Model‐Based Analysis of Endogenous Biomarker Kinetics. (23rd August 2018) - Yoshida, Kenta; Guo, Cen; Sane, Rucha
Abstract : Quantitative prediction of the magnitude of transporter‐mediated clinical drug‐drug interactions (DDIs) solely from in vitro inhibition data remains challenging. The objective of the present work was to analyze the kinetic profile of an endogenous biomarker for organic anion‐transporting polypeptides 1B (OATP1B), coproporphyrin I (CPI), and to predict clinical DDIs with a probe OATP1B substrate (pravastatin) based on " in vivo " inhibition constants (Ki ). The CPI kinetics in the presence and absence of strong and weak OATP1B inhibitors (rifampin and GDC‐0810) were described well with a one‐compartment model, and in vivo Ki were estimated. Clinical DDIs between pravastatin and these inhibitors were predicted using physiologically based pharmacokinetic (PBPK) models coupled with the estimated in vivo Ki and predicted magnitude matched well with the observed DDIs. In conclusion, model‐based analysis of the CPI profile has the potential to quantitatively predict liability of a new molecular entity (NME) as an OATP1B inhibitor early in drug development.